2019
DOI: 10.5761/atcs.ra.18-00229
|View full text |Cite
|
Sign up to set email alerts
|

The Past, Present and Future of Pulmonary Metastasectomy: A Review Article

Abstract: Pulmonary metastases are a sign of advanced malignancy and an omen of poor prognosis. Once primary tumors metastasize, they become notoriously difficult to treat and interdisciplinary management often involves a combination of chemotherapy, radiotherapy, and surgery. Over the last 25 years, the emerging body of evidence has recognized the curative potential of pulmonary metastasectomy. Surgical resection of pulmonary metastases is now commonly considered for patients with controlled primary disease, absence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 88 publications
(243 reference statements)
3
53
0
3
Order By: Relevance
“…The local aggressive treatment potentially extends survival in patients with pulmonary oligometastases of various primary cancers. 1,2 While pulmonary metastasectomy is the standard treatment for patients with a limited metastatic pattern, several retrospective studies have shown that x-ray stereotactic body radiation therapy (SBRT) yields short-term promising outcomes that are comparable to those of surgery. 3,4 Proton beam therapy (PBT) can reduce the volume of and radiation dose to the surrounding normal tissues using the sharp Bragg peak fall-off, as demonstrated in previous dosimetry studies.…”
Section: Introductionmentioning
confidence: 99%
“…The local aggressive treatment potentially extends survival in patients with pulmonary oligometastases of various primary cancers. 1,2 While pulmonary metastasectomy is the standard treatment for patients with a limited metastatic pattern, several retrospective studies have shown that x-ray stereotactic body radiation therapy (SBRT) yields short-term promising outcomes that are comparable to those of surgery. 3,4 Proton beam therapy (PBT) can reduce the volume of and radiation dose to the surrounding normal tissues using the sharp Bragg peak fall-off, as demonstrated in previous dosimetry studies.…”
Section: Introductionmentioning
confidence: 99%
“…Some other prognostic factors of survival have been described in the literature, but were not identified as statistically significant in our series: DFI1; completeness of resection; presence of lymph node metastases; number and size of pulmonary metastases; female sex [ 2 ]. The primary tumor histology has been identified as a prognostic factor in many studies [ 1 , 2 , 17 , 18 ]. The International Registry of Lung Metastases reported a better survival rate for patients with germ cell tumors (68% at 5 years), followed by epithelial tumors (37% at 5 years), sarcomas (31% at 5 years) and melanoma (21% at 5 years) [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…DFI is reported to be an important prognostic factor after PM in various types of cancers [ 18 ]. Cormio et al [ 3 ] reported that patients with shorter DFI had a poor prognosis in patients with distant metastasis from ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%